Pengaruh Strategi Pembelajaran Swa-Atur dengan Discovery Learning dan Gaya Kognitif terhadap Hasil Belajar Kimia - Mohammad Fauzi; Rufi'i; Achmad Noor Fatirul (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2019)
The objectives of this study were 1) to determine differences in chemistry learning outcomes between students who took Self-Organized learning strategies and Discovery Learning, 2) to determine differences in chemistry learning outcomes between students who had Field Dependence cognitive style and Field Independence cognitive style, and 3) to determine the interaction between Self-Organized learning, Discovery Learning learning, and students' cognitive styles on chemistry learning outcomes. This research is a 2 x 2 factorial experimental research. The control group is a group that follows learning using the Discovery Learning learning strategy, while the experimental group is a group that takes learning using the Self-Organized learning strategy. Through this two-way ANAVA analysis design, the influence of Self-Arranged learning strategy with Discovery Learning learning strategy and students' cognitive style, namely Field Dependence and Field Independence, will be compared to chemistry learning outcomes. From the analysis, the results obtained: Ha.1, it is obtained that Fcount = 22.566 is greater than Ftable with the numerator 1 and denominator 67 which is 3.99 (Fcount> Ftable) and p = 0.000 then p <0.05, so it is proven that the average value of the two populations not the same so it is evident that the learning outcomes with Self-Organized learning strategies and Discovery Learning differ significantly at the 95% confidence level. Ha.2 obtained Fcount = 5.182 greater than Ftable with a numerator of 1 and the denominator 67 is 3.99 (Fcount> Ftable) and p = 0.000 so p <0.05 means that the learning outcomes of students who have Field Independence cognitive style and Field Dependence cognitive style are different significantly at the 95% confidence level, and Ha.3 obtained Fcount = 0.219 which is smaller than Ftable with numerator 1 and denominator 67 is 3.88 (Fcount <Ftable) and p = 0.641 then p> 0.05 means that there is no interaction between self-learning strategies -Set and Discovery Learning and students' cognitive styles on learning outcomes at the 95% confidence level. The conclusion was that students who were given the Self-Organized learning strategy showed higher learning outcomes than Discovery Learning learning strategies. That students who have Field Independence have higher learning outcomes than students who have Field Dependence. There is no interaction between learning strategies and chemistry learning outcomes.